Natural Products in the Chemical Industry - Schäfer, Bernd (SpringerLink Bücher, 2014)
Natural Products in the Chemical Industry is not a conventional textbook, but rather an invitation to join an entertaining journey that takes you into the fascinating world of natural products. This book features diverse compound classes from a number of areas: colourants, fragrances and flavourings, amino acids, pharmaceuticals, hormones, vitamins and agrochemicals. Whether you are a teacher or a scholar, an undergraduate or graduate student, a professional chemist in industry or academia, or someone just interested in natural sciences, this book allows you to be inspired and entertained by facts and information along with enjoyable anecdotes, historical, economic, political, biological and social considerations. Experts in the field can have a pleasurable time cruising through captivating synthesis methods, which enable the generation of complex molecules on industrial scale. This book · deals with the manufacturing of larger quantities of complex molecules (asymmetric and heterocyclic compounds, polycyclic structures, macrocycles and small rings) · displays all reaction schemes in colour, which makes them easy to read · highlights aesthetics and elegance in modern industrial organic chemistry